2020
DOI: 10.3390/su12229577
|View full text |Cite
|
Sign up to set email alerts
|

Price Differentiation and Inventory Decisions in a Socially Responsible Dual-Channel Supply Chain with Partial Information Stochastic Demand and Cannibalization

Abstract: Corporate social responsibility (CSR) has received much of the attention in supply chain management, in particular the pricing decisions. Most existing models that enable CSR integration into pricing decisions in a supply chain context assume deterministic demand and focus on a single distribution channel. Despite the fact that dual-channel supply chain (DCSC) has received popularity, most pricing decisions models in DCSC assume fixed and deterministic market share distribution between channels, and no demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 113 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…A robust and nearly optimal decentralized assignment approach is developed to fulfill the hierarchical random demand. More relevant studies can be found in the recent literature [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A robust and nearly optimal decentralized assignment approach is developed to fulfill the hierarchical random demand. More relevant studies can be found in the recent literature [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Johari et al [14] analyzed coordinated joint pricing and periodic review ordering choices for a supply chain with stochastic pricedependent demand. Most recent studies on stochastic inventory problems include Claudio et al [15], Luo et al [16], Achin and Sunil [17], Raza [18], Mario et al [19], Malek et al [20], Tai et al [21], Momeni and Afshar-Nadjafi [22], and Li et al [23].…”
Section: Introductionmentioning
confidence: 99%